The decline of clinical laboratory science programs in colleges and universities. - Castillo JB (Journal of Allied Health)
Enrollment in clinical laboratory science (CLS) programs has declined over 50% since 1980. This has led to the closure of many CLS programs while putting others at risk. This article examines the environmental changes that have occurred since the early 1980s and their impact on CLS programs and enrollment. Recommendations for CLS programs and Schools of Allied Health for adaptation to these changes are also made.